Pengaruh Tingkat Digitalisasi Perbankan dan Implementasi ESG terhadap Nilai Saham Studi Empiris Periode 2022-2024 - Putri Irmala Sari; Supri Yanto (Komunitas Dosen Indonesia, 2025)
This research investigates the impact of banking digitalization and Environmental, Social, and Governance (ESG) implementation on BUKU IV bank share values in Indonesia. The study employs a quantitative methodology using quarterly panel data from 2022-2024, focusing on BUKU IV banks listed on the Indonesia Stock Exchange, selected through purposive sampling. The research examines two primary independent variables - the Digital Banking Index and ESG Score - along with fundamental factors. Share valuation assessment utilizes both Price-to-Book Value (PBV) and Tobin's Q calculations, with data analysis conducted through multiple linear regression using SPSS version 25. The findings demonstrate that banking sector digitalization and ESG implementation both positively influence share valuations, with the Digital Banking Index showing stronger impact than the ESG Score. This indicates investors place greater emphasis on digital capabilities in their banking valuations. Additionally, fundamental factors maintain their significance in determining share values. These results provide strategic insights for enhancing firm value through digital transformation and strengthened ESG practices. The study contributes to banking valuation methodology by presenting an integrated model that incorporates both digital and sustainability aspects, establishing a framework for evaluating bank performance in the contemporary digital environment.